Ingested partial denture mimicking perforated diverticular disease - Wehrmann, Fabian (J Surg Case Rep, 2019)
Denture ingestion is a rare clinical entity among foreign body ingestions. The caveat is that there is often no recollection of the event and that dentures are radiolucent and as such hard to identify on conventional imaging. To date not all dentures contain radiopaque marker. Here we present the case of a 52-year-old male who was admitted with clinical and radiological signs of perforated diverticular disease. A curvilinear metallic foreign body was picked up on repeat CT imaging at day 3, which was part of an unknowingly swallowed partial denture that became impacted and perforated the sigmoid colon. The patient underwent an uneventful laparoscopic anterior resection and was discharged home a week later. We conclude that all dentures should contain a radiopaque marker in order to avoid failure in radiological detection and thus prevent misdiagnosis and inappropriate treatment.